Monetary Dynamics: Comparative Analysis of the Dual Policies of Malaysia and Indonesia - Fitria Rahmah; Rini Ariyanti; Dwi Handika; Tika Parlina (Journal of Islamic Economics and Business, 2025)
Economic stability is a key indicator of macroeconomic health, directly influenced by the effectiveness of monetary policies implemented by national authorities. This study investigates the monetary dynamics and the impact of dual monetary policies on economic stability in Malaysia and Indonesia. Dual monetary policy involves the simultaneous application of both conventional and sharia-based instruments to achieve macroeconomic objectives such as price stability, economic growth, and inflation control. The study employs Partial Least Squares Structural Equation Modeling (SEM-PLS) with Multi-Group Analysis (MGA) to compare the effectiveness of these policies between the two countries using quarterly data from 2016 to 2024. The results indicate that dual monetary policies significantly influence economic stability in both countries, albeit with different leading instruments. In Indonesia, the Minimum Reserve Requirement (GWM) is the most influential component, while in Malaysia, the Discount Rate holds the most weight. However, no statistically significant differences were found between the two contexts. These findings highlight the strategic importance of integrating conventional and sharia-based instruments to enhance economic resilience in dual financial systems.